Prognostic functional MR imaging parameters in head and neck squamous cell carcinoma: A systematic review. Issue 144 (November 2021) - Bos, Paula; van der Hulst, Hedda J.; van den Brekel, Michiel W.M.; Schats, Winnie; Jasperse, Bas; Beets-Tan, Regina G.H.; Castelijns, Jonas A.
Graphical abstract: Highlights: Functional MRI markers are prognostic for treatment outcome in head and neck cancer. Perfusion markers are promising for clinical treatment response prognostication. Findings of diffusion markers show high variety due to study design heterogeneity. To reduce heterogeneity, several points of advice for future research are provided. Abstract: Objective: Functional MR imaging has demonstrated potential for predicting treatment response. This systematic review gives an extensive overview of the current level of evidence for pre-treatment MR-based perfusion and diffusion imaging parameters that are prognostic for treatment outcome in head and neck squamous cell carcinoma (HNSCC) (PROSPERO registrationCRD42020210689). Materials and methods: According to the PRISMA statements, Medline, Embase and Scopus were queried for articles with a maximum date of October 19th, 2020. Studies investigating the predictive performance of pre-treatment MR-based perfusion and/or diffusion imaging parameters in HNSCC treatment response were included. All prognosticators were extracted from the primary tumor. Risk of bias was assessed using the QUIPS tool. Results were summarized in tables and forest plots. Results: 31 unique studies met the inclusion criteria; among them, 11 articles described perfusion (n = 529 patients) and 28 described diffusion (n = 1626 patients) MR-imaging, eight studies were included in both categories. Higher K trans and Kep were associated with better treatment response for OS and DFS, respectively. Study findings for Vp and Ve were inconsistent or not significant. High-level controversy was observed between studies examining the MR diffusion parameters mean and median ADC. Conclusion: For HNSCC patients, the accurate and consistent results of pre-treatment MR-based perfusion parameters K trans and Kep are potential for clinical applicability predictive of OS and DFS and treatment decision guidance. Significant heterogeneity in study designs might affect high discrepancy in study results for parameters extracted from diffusion imaging. Furthermore, recommendations for future research were summarized.